Consumer's Reactions to Natural, Atypically Colored Foods: An Investigation Using Blue Potatoes. Issue 1 (21st December 2015) - Paakki, Maija; Sandell, Mari; Hopia, Anu
Abstract: This study's aim was to investigate a consumer's reactions to foods that are naturally atypically colored. Blue potatoes were used, and we characterized consumers who chose either familiar, yellow potatoes, or unfamiliar, blue potatoes. Volunteers ( n  = 235) were asked to rate their perceptions after tasting blue or yellow potato salad by using an 8‐point Likert scale. Second, they were asked to choose between yellow and blue potatoes and argue their choice. Subgroups were classified into "yellow potato choosers" (64.7% of participants) and "blue potato choosers" (28.1% of participants) and each evaluated yellow potato salad quite equally, but "yellow potato choosers" rated blue potato salad lower than "blue potato choosers." "Blue potato choosers" tended to be more neophilic and middle‐aged compared to "yellow potato choosers." "Yellow potato choosers" were traditional consumers who chose yellow potatoes because of their taste and familiarity. "Blue potato choosers" tended to be more hedonistic and variety‐seeking as their willingness to try new things and appearance of food seemed to be important factors behind their choice of atypically colored blue potatoes. Practical Applications: This study demonstrated that an atypical color of an ordinary food product (potatoes) affected participants' perceptions and choice in consumer research. Although most consumers preferred typically colored yellow potatoes, over a quarter of the participants were willing to choose blue potatoes. Quite differently behaving consumer groups were found by segmentation of the volunteers according to their choice between yellow and blue potatoes. For instance, naturalness is generally considered as one of the key attributes behind food choice, but among "blue potato choosers" in our study it was not an important factor behind their potato choice. Our findings can assist food scientists and product developers in understanding the impact of an atypical color – and more widely nonfamiliar characteristics present in foods – on the perception of food and food choice.